Trophic Actions of Oral Vanadium and Improved Glycemia on the Pancreatic Beta-Cell Ultrastructure of Streptozotocin-Induced Diabetic Rats - Mohammadi, Mohammad Taghi; Pirmoradi, Leila; Mesbah, Fakhrodin; Safaee, Akbar; Dehghani, Gholam Abbas (JOP. Journal of the Pancreas, 2014)
Context Oral vanadyl sulfate (vanadium) has potent hypoglycemic effects in diabetes animals, but data about its actions on pancreatic beta-cells (BC) ultrastructure is limited. Objective Partial diabetic rats were treated with vanadium and insulin injection and their effects on BC ultrastructure are studied. Methods Male rats were made diabetic with intravenous streptozotocin injection (STZ, 40 mg/kg). Animals were randomly divided to control (CD), vanadium-treated (1 mg/mL VOSO4 + 5H2O in base solution, VTD) and insulin-treated (80 U/kg/day NPH insulin injection, ITD) diabetic groups. Treatments started 10 days after STZ injection and terminated after 2 months. Intermittent tail blood samples were taken for measurements of blood glucose (BG) and plasma insulin (PI). Finally animals were sacrificed and pancreata prepared for assessments of BC ultrastructure, islets histology and insulin immunoreactivity (IIR). Results Vanadium decreased BG (P<0.0001), elevated the reduced PI (P<0.001), prevented islet atrophy and restored BC ultrastructure. Low BG seen during treatment in VTD and ITD only persisted in VTD after vanadium withdrawal. Hyperglycemia worsened in CD and repaired in ITD shortly after insulin withdrawal. CD islets were atrophied, had scattered IIR spots. BC had pyknotic nuclei, vacuolated cytoplasm and few tiny insulin secretory granules. VTD islets looked normal with compact centered IIR spots. BC had well-developed endoplasmic reticulum, many insulin secretory granules and mitochondria. ITD islet structure was slightly better than CD and BC had some immature insulin secretory granules. Conclusion The trophic actions of vanadium in diabetic rats effectively renovated beta cell ultrastructure and prevented pancreatic islets atrophy, whereas the relief of glucotoxicity seen with insulin treatment could repair some beta cells and partially prevented islet atrophy. Image: Toluidine blue staining of the pancreatic tissues of insulin-treated diabetic (ITD) rats.